2020
DOI: 10.1017/s0950268820002046
|View full text |Cite
|
Sign up to set email alerts
|

The Global Health Security index and Joint External Evaluation score for health preparedness are not correlated with countries' COVID-19 detection response time and mortality outcome

Abstract: Global Health Security Index (GHSI) and Joint External Evaluation (JEE) are two well-known health security and related capability indices. We hypothesised that countries with higher GHSI or JEE scores would have detected their first COVID-19 case earlier, and would experience lower mortality outcome compared to countries with lower scores. We evaluated the effectiveness of GHSI and JEE in predicting countries' COVID-19 detection response times and mortality outcome (deaths/million). We used two different outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
96
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(109 citation statements)
references
References 15 publications
(44 reference statements)
12
96
0
1
Order By: Relevance
“…Previous analyses have not found an association between preparedness measures and COVID-19 case counts or incidence, and have questioned the value of the JEE process. 4,5,6 We find that preparedness scores do in fact correlate with pandemic severity, but that this association is only apparent after adjusting for testing rates, which we identified as a confounding variable. The JEE is a useful tool to measure country progress on achieving the IHR (2005) commitments and provide the necessary planning framework that can be costed and implemented into a fully functional action plan.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Previous analyses have not found an association between preparedness measures and COVID-19 case counts or incidence, and have questioned the value of the JEE process. 4,5,6 We find that preparedness scores do in fact correlate with pandemic severity, but that this association is only apparent after adjusting for testing rates, which we identified as a confounding variable. The JEE is a useful tool to measure country progress on achieving the IHR (2005) commitments and provide the necessary planning framework that can be costed and implemented into a fully functional action plan.…”
Section: Discussionmentioning
confidence: 67%
“…12 We found substantial covariance among these three measures, and focused on JEE scores for capacity measurement; the correlations among these measures have been published elsewhere. 4,5,6…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We further found that countries with higher median age had higher CFR value. Older age has been recognized as one of the most common risk factors for a severe outcome of COVID-19 [99][100][101]. A study conducted with 5,484 patients in Italy found the CFR of COVID-19 was 0.43% for people below 70 years and 10.5% for people above 70 years and above [101].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, from these published studies, we noted that anti-epidemic measures at the national level often performed inadequately in predicting disease burdens emanating from the COVID-19 pandemic. 3 , 4 …”
Section: Introductionmentioning
confidence: 99%